(untitled) (Fiep Bulletin - online, 2014)
The aim of this study was to analyze the teaching practice of Physical Education teachers ofBasic Education - second cycle, from the 5th to the 8th grade, called Ensino Fundamental, stressing the values related to Ecology and Environmental Education (EE). The setting of the search was the public schools of the major cities in the Vale do Aço region: Coronel Fabriciano, Ipatinga and Timóteo, in the state of Minas Gerais. In a universe of 64 teachers, 35 were selected to be part of the sample. It was used a semi-structured interview, elaborated after the reading and study of references related to the objective of this search, giving emphasis to the Brazilian National Curriculum for Physical Education and Environment and Health (Parâmetros Curriculares Nacionais - PCN). The interview was recorded, done individually, in place and schedule established by the teacher. Later on, the answers were written out in total and analyzed, having Bardin (2002) as methodological parameter. Among the 35 interviewed teachers, 12 do not include the Environmental Education theme in their annual planning, and 23 include it. As to the knowledge of the subject matter and reading of the PCN, 20 don’t know them and 15 know and have read them. Thirty-two teachers consider the topic appropriate to be worked in Physical Education classes and 3 do not. Seventeen worked with it in an interdisciplinary way and 18 did not. Thirty-four teachers consider that EE contributes to the development of new knowledge and abilities, values and attitudes, having in mind the improvement of the environmental quality. Although 26teachers said they don’t work with this theme, 23 of them include it in their annual planning. This way, it can be concluded that the teaching practice of Physical Education teachers doesn’t stress the values related to Ecology and Environmental Education.